Adoption factors of forage innovations in cattle production systems in the northwest highlands of Vietnam - Bravo, Aura; Florez, Fernando; Dao, Hang Thi; Nguyen, Thinh; Atieno, Mary; Triana Ángel, Natalia; Hoang, Thao Xuan; Tran, Ngoc Thi Bich; Peters, Michael; Burkart, Stefan (2024)
Winter feed shortage, poor quality of available feed resources, and limited knowledge of suitable forage types, management, and utilisation are some challenges faced by livestock producers in the Northwest Highlands (NWH) of Vietnam. Context-specific feeding intervention strategies were designed and implemented to address these issues in Son La province, NWH. These are promoting the uptake of improved forage varieties (grasses and legumes) and capacity building on animal nutrition, including feed processing and preservation, and feeding regimens for cattle and pigs, respectively. Initial results show the potential of feed and forage technologies in improving livestock productivity in the region. This study aims at identifying the inhibiting and promoting adoption factors of seven improved forage technologies in the Chieng Luong and Chieng Chung communes, Mai Son District, Son La Province. A qualitative approach is chosen to fathom out the determinants of farmers’ individual decisions when adopting these innovations for sustainable livestock production. The categories evaluated are based on the framework proposed by Ndah et al. (2022): 1) the individual characteristics predisposing to the acceptance or rejection of the technology; 2) attributes, knowledge, and challenges of technology use (known or perceived); and 3) contextual characteristics that create an enabling environment to stimulate adoption. Key informant interviews and focus group discussions will be conducted with cattle farmers (adopters and non-adopters, men and women) and other actors from the cattle value chain. The expected results will contribute to the efforts underway for designing integrated models for the delivery, adoption, and scaling of such technologies and knowledge in Vietnam, and give insights for scaling across the Southeast Asian region.